Reconstructing the Late Pleistocene – Anthropocene interaction between the neotectonic and archaeological landscape evolution in the Apennines (La Sassa cave, Italy). (1st August 2021) - Alessandri, L.; Cardello, G.L.; Attema, P.A.J.; Baiocchi, V.; De Angelis, F.; Del Pizzo, S.; Di Ciaccio, F.; Fiorillo, A.; Gatta, M.; Monti, F.; Onori, M.; Rolfo, M.F.; et al.
Abstract: Caves are one of the most conservative environments on Earth, where archaeological, anthropological, climatic and tectonic data can be well-preserved. Here, we present the results of a multidisciplinary method that allowed us to recognize, for the first time in this area, the interaction between Late Pleistocene to Anthropocene neotectonic and archaeological evolutionary stages of a cave of the Apennines (La Sassa cave), that encompass also its surroundings (Volsci Range and Pontina Plain). Both structural and 3D survey highlighted a step-wise shape of the cave due to normal fault steps that allowed the localized formation of concretions also enveloping archaeological layers. Sixteen 14 C ages on fauna and human bones and thousands of archaeological finds provided chronological constraints of faulting in the Late Pleistocene and possibly also after the Middle Bronze Age. In the frame of a region that was not previously recognized as tectonically active, the structural evidence is relevant for understanding the speleogenesis of the cave from the Late Pleistocene and its human occupation. Burial and ritual activities in the cave from the Copper Age to the Middle Bronze Age have been recognized with implications on possible settlement pattern schemes with the La Sassa cave as a "persistent place" in the prehistoric human landscape. The analyses of the ceramic style in a regional framework also suggests the presence of a cultural boundary near La Sassa, which becomes highly osmotic just after the beginning of the Middle Bronze Age. The La Sassa findings provide as well implications for the seismic hazard assessment in a region inhabited by about 0.4 million people. Highlights: Neotectonic evolution is documented for the first time in Quaternary underground settings nearby Rome. Structural evidence and dating constrain the speleogenesis of caves from the Late Pleistocene to their human occupation. The cave was used as a funerary site in the Copper Age and Early Bronze Age and as a cultic place in the Middle Bronze Age. In the Middle Bronze Age, funerary caves acted as "persistent places".